Amiodarone impairs trafficking through late endosomes inducing a Niemann-Pick C-like phenotype - Piccoli, Elena (Biochem Pharmacol, 2011)
Patients treated with amiodarone accumulate lysobisphosphatidic acid (LBPA), also known as bis(monoacylglycero)phosphate, in airway secretions and develop in different tissues vacuoles and inclusion bodies thought to originate from endosomes. To clarify the origin of these changes, we studied in vitro the effects of amiodarone on endosomal activities like transferrin recycling, Shiga toxin processing, ESCRT-dependent lentivirus budding, fluid phase endocytosis, proteolysis and exosome secretion. Furthermore, since the accumulation of LBPA might point to a broader disturbance in lipid homeostasis, we studied the effect of amiodarone on the distribution of LBPA, unesterified cholesterol, sphingomyelin and glycosphyngolipids. Amiodarone analogues were also studied, including the recently developed derivative dronedarone. We found that amiodarone does not affect early endosomal activities, like transferrin recycling, Shiga toxin processing and lentivirus budding. Amiodarone, instead, interferes with late compartments of the endocytic pathway, blocking the progression of fluid phase endocytosis and causing fusion of organelles, collapse of lumenal structures, accumulation of undegraded substrates and amassing of different types of lipids. Not all late endocytic compartments are affected, since exosome secretion is spared. These changes recall the Niemann-Pick type-C phenotype (NPC), but originate by a different mechanism, since, differently from NPC, they are not alleviated by cholesterol removal. Studies with analogues indicate that basic pKa and high water-solubility at acidic pH are crucial requirements for the interference with late endosomes/lysosomes and that, in this respect, dronedarone is at least as potent as amiodarone. These findings may have relevance in fields unrelated to rhythm control.